Esthetic Rehabilitation of the Smile with No-Prep Porcelain Laminates and Partial Veneers - Arcelino Farias-Neto; Edna Maria da Cunha Ferreira Gomes; Alfonso Sánchez-Ayala; Alejandro Sánchez-Ayala; Larissa Soares Reis Vilanova (Hindawi Limited, 2015)
Rehabilitation of patients with anterior conoid teeth may present a challenge for the clinician, especially when trying to mimic the nature with composite resins. This clinical report exemplifies how a patient with conoid upper lateral incisors was rehabilitated with minimally invasive adhesive restorations. Following diagnostic wax-up and cosmetic mock-up, no-prep veneers and ceramic fragments (partial veneers) were constructed with feldspathic porcelain. This restorative material presents excellent reproduction of the optical properties of the dental structure, especially at minimal thicknesses. In this paper, the details about the treatment are described. A very pleasing outcome was achieved, confirming that minimally invasive adhesive restorations are an excellent option for situations in which the dental elements are healthy, and can be modified exclusively by adding material and the patient does not want to suffer any wear on the teeth.